Profiling of injuries sustained during 2018 football tournament: An observational study - Adiele, D.; Morgan, G. D. P.; Carolyne, L. M. (Journal of Sports Medicine & Doping Studies, 2018)
Objective: This study aims at documenting the incidences, nature and severity of injuries on the Kingdom of Swaziland football players. In addition, we investigate the association between injury incidence rates (IRs), players` age and playing positions.